In silico Characterization of bHLH Transcription Factor Genes in the Genome of Rainbow Trout (Oncorhynchus mykiss) - ÇELİK ALTUNOĞLU, Yasemin; DEDEELİ, Gülsüm (Marine Science and Technology Bulletin, 2021)
The significance of seafood in nutrition has started to be better understood after the change in the understanding of nutrition in the world. One of the most common species cultivated in the world is rainbow trout (Oncorhynchus mykiss) from the origin of North America. Transcription factors are a group of proteins containing different functional components for the accomplishment of various activities. The basic helix (bHLH) domain is a highly preserved amino acid motif that characterizes a family of transcription factors. The bHLH gene family in the rainbow trout (Oncorhynchus mykiss) genome has been identified in the current study for the first-time using bioinformatics tools. According to the results, 441 bHLH genes (OmybHLH) were identified in the rainbow trout genome and the physicochemical properties of those proteins were determined. The highest number of the genes was in 7th chromosome of rainbow trout with 29 OmybHLH genes. 38 of OmybHLH genes had no intronic regions. OmybHLH proteins were divided into 4 main groups in the phylogenetic tree consistent with their motif content. The common biological function of OmybHLH proteins was the regulation of biological processes. The mode of action of OmybHLH proteins was binding activity. The OmybHLH gene family in the rainbow trout and the bHLH gene family in the Atlantic salmon (SsabHLH) had 95 orthologous gene relationships and average separation times of those orthologous genes were found to be 298 million years ago (MYA). Almost all the OmybHLH protein family members have dominated by the α-helix motif which is a stable conformation. Identification of the bHLH proteins and evaluation of their properties in rainbow trout can open new perspectives for aquaculture applications and fish culture to get better yield using genetic data.
Keywords: Structural Biology; Yapısal Biyoloji; bHLH gene family; Genome-wide analysis; Oncorhynchus mykiss; Transcription factors; 14. Life underwater